Exploring Students’ Difficulties In Learning Qualitative Research Methods In Higher Education - Sudirman Sudirman; Edi Firman (Lembaga Penelitian dan Pendidikan Mandala, 2026)
Learning qualitative research methods has become an essential component of higher education, particularly in English Education programs where students are expected to develop research competence and academic literacy. However, many undergraduate students continue to experience difficulties in understanding and applying qualitative inquiry in research methodology courses. This study aimed to explore students’ difficulties in learning qualitative research methods in higher education. The study employed a qualitative case study approach involving undergraduate students from an English Education Department at a private university in Indonesia. The participants were selected purposively based on their experience in taking research methodology courses and conducting qualitative research projects. Data were collected through semi-structured interviews and reflective documents and analyzed using thematic analysis. The findings revealed four major challenges experienced by students: difficulties in understanding qualitative research concepts, challenges in developing research problems and research questions, difficulties in conducting qualitative data analysis, and limited confidence in conducting independent qualitative research. The findings also indicated that practical learning activities, lecturer feedback, and collaborative discussion contributed positively to students’ methodological understanding. This study highlights the importance of implementing student-centered and practice-oriented instructional approaches in qualitative research methodology courses to support students’ analytical competence and research readiness in higher education. The findings offer practical implications for research methodology lecturers and curriculum developers, particularly in designing more experiential, reflective, and mentorship-based learning strategies to strengthen students’ qualitative research competence in higher education